2022
DOI: 10.1111/cns.13899
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic microglia and macrophages in brain injury and repair

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 186 publications
(475 reference statements)
2
35
0
Order By: Relevance
“…Shi et al reported that the function of Treg cells in facilitating oligodendrogenesis and remyelination was mediated by promoting tissue‐reparative microglia responses following crosstalk with microglia at the chronic stage of stroke 86 . It was reported that ischemic postconditioning (reperfusion for 10 min after which the middle cerebral artery was reoccluded for 10 min) for one episode can facilitate to shift microglia into tissue repairing forms, 52 which actively participate in myelin repair 87,88 . In addition, a recent study confirmed the contribution of RIC is linked to Treg cells thriving.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 94%
“…Shi et al reported that the function of Treg cells in facilitating oligodendrogenesis and remyelination was mediated by promoting tissue‐reparative microglia responses following crosstalk with microglia at the chronic stage of stroke 86 . It was reported that ischemic postconditioning (reperfusion for 10 min after which the middle cerebral artery was reoccluded for 10 min) for one episode can facilitate to shift microglia into tissue repairing forms, 52 which actively participate in myelin repair 87,88 . In addition, a recent study confirmed the contribution of RIC is linked to Treg cells thriving.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 94%
“…Microglia also can engulf infiltrating immune cells in the injured brain and modulate their pro-inflammatory properties (Yu et al, 2022 ). Microglia clear granulocytes within 24 h after ischemia insults to attenuate apoptosis of neurons (Neumann et al, 2008 ).…”
Section: Microglial Crosstalk With Other Cellular Brain Partnersmentioning
confidence: 99%
“…Through both M1 and M2 microglia own phagocytic receptors, the M2 phenotype has higher phagocytic capabilities to clear dead neurons than the M1 phenotype 52 . The M1 phenotype inaccurately engulfs normal neurons, while the M2 phenotype has neuroprotection through antioxidant functions 53 …”
Section: Introductionmentioning
confidence: 99%
“… 52 The M1 phenotype inaccurately engulfs normal neurons, while the M2 phenotype has neuroprotection through antioxidant functions. 53 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation